The myth of TQM in knowledge management systems - Costa, Gonçalo Jorge Morais da (2014)
The paper endeavours to debate the myth of total quality management (TQM) in knowledge management systems (KMS), i.e., the authors will demonstrate that KMS have not achieved total quality. The reasons for this claim are: (i) organisational knowledge management (OKM) (stricto sensu) comprises a blend between individual and collective sense making; (ii) their dialectic process raises ethical and social issues despite the context (more or less technological); (iii) quality is an ambiguous and subjective concept; and, (iv) total quality management is a philosophy of management (potential multiple interpretations). Through several empirical evidences from the first co-author PhD work and professional experiences, a novel framework will be proposed. Finally, this contribution argument will be divided into 5 sections: (i) the hierarchy of DIKW; (ii) knowledge management; (iii) total quality management; (iv) KMS versus TQM; and, (v) discussion.